Detection of fast (40–150 Hz) oscillations from the ictal scalp EEG data of myoclonic seizures in pediatric patients - Kobayashi, Katsuhiro; Ohuchi, Yuji; Shibata, Takashi; Hanaoka, Yoshiyuki; Akiyama, Mari; Oka, Makio; Endoh, Fumika; Akiyama, Tomoyuki (Brain & development (Tokyo. 1979), 2018)
We explored fast (40–150 Hz) oscillations (FOs) from the ictal scalp electroencephalogram (EEG) data of myoclonic seizures in pediatric patients to obtain insight into the pathophysiological mechanisms involved in the generation of myoclonic seizures. The participants were 21 children (11 boys, 10 girls; age ranging from 5 months to 17 years 2 months) with myoclonic seizures associated with generalized (poly)spike-wave bursts in the ictal EEG data. The patients had heterogeneous etiologies and epilepsy diagnoses. In the ictal data, we detected FOs that clearly showed oscillatory morphology in filtered EEG traces and an outstanding spectral blob in time-frequency analysis. We identified FOs in 61 (88.4%) of all 69 myoclonic seizures. Every patient had at least one myoclonic seizure-associated FO. The observed FOs were embedded in the spike component of (poly)spike-wave discharges, and they had a focal distribution with frontal predominance. They ranged in frequency from 41.0 to 123.0 Hz and involved both the gamma and ripple bands, and their spectral peak frequencies were higher in the group of patients with a genetic background free of apparent fundamental brain pathology than in the group of other patients (p = 0.019). FOs were found to represent at least part of the cortical pathophysiological process in the generation of myoclonic seizures that should involve the thalamocortical network system.